Ascochlorin is a novel, specific inhibitor of the mitochondrial cytochrome bc(1) complex - Berry, Edward A. (2009)
Ascochlorin is an isoprenoid antibiotic that is produced by the phytopathogenic fungus Ascochyta viciae. Similar to ascofuranone, which specifically inhibits trypanosome alternative oxidase by acting at the ubiquinol binding domain, ascochlorin is also structurally related to ubiquinol. When added to the mitochondrial preparations isolated from rat liver, or the yeast Pichia (Hansenula) anomala, ascochlorin inhibited the electron transport via CoQ in a fashion comparable to antimycin A and stigmatellin, indicating that this antibiotic acted on the cytochrome bc(1) complex. In contrast to ascochlorin, ascofuranone had much less inhibition on the same activities. On the one hand, like the Q(i) site inhibitors antimycin A and funiculosin, ascochlorin induced in H. anomala the expression of nuclear-encoded alternative oxidase gene much more strongly than the Q(o) site inhibitors tested. On the other hand, it suppressed the reduction of cytochrome b and the generation of superoxide anion in the presence of antimycin A(3) in a fashion similar to the Q(o) site inhibitor myxothiazol. These results suggested that ascochlorin might act at both the Q(i) and the Q(o) sites of the fungal cytochrome bc(1) complex. Indeed, the altered electron paramagnetic resonance (EPR) line shape of the Rieske iron-sulfur protein, and the light-induced time resolved cytochrome b and c reduction kinetics of Rhodobacter capsulatus cytochrome bc(1) complex in the presence of ascochlorin demonstrated that this inhibitor can bind to both the Q(o) and Q(i) sites of the bacterial enzyme. Additional experiments using purified bovine cytochrome bc(1) complex showed that ascochlorin inhibits reduction of cytochrome b by ubiquinone through both Q(i) and Q(o) sites. Moreover, crystal structure of chicken cytochrome bc(1) complex treated with excess ascochlorin revealed clear electron densities that could be attributed to ascochlorin bound at both the Q(i) and Q(o) sites. Overall findings clearly show that ascochlorin is an unusual cytochrome bc(1) inhibitor that acts at both of the active sites of this enzyme.